Degradation and mineralization of tetracycline and oxytetracycline by Fenton process: effect of inorganic anions - Gurtekin, Engin; Celik, Aytekin; Aydin, Ekrem (Elsevier Science Inc, 2022)
In this study, the effect of inorganic anions (Cl-, SO42-, NO3-, CO32- and HCO3-) on degradation and mineralization of tetracycline (TC) and oxytetracycline (OTC) with Fenton process was investigated. For this purpose, concentrations of 1, 10 and 100 mM of inorganic anions were used in this study. Tetracycline and oxytetracycline degradation is 100% at the inorganic anion concentrations studied. The degree of mineralization of TC was 66%, 64%, 64%, 62%, 65% and 43% at control, 1 mM Cl-, SO42-, NO3-, CO32- and HCO3-, respectively. The degree of mineralization of OTC was 49%, 47%, 49%, 47%, 47% and 40% at control, 1 mM Cl-, SO42-, NO3-, CO32- and HCO3-, respectively. The degree of mineralization of TC was 66%, 71%, 70%, 71%, 74% and 74% at control, 10 mM Cl-, SO42-, NO3-, CO32- and HCO3-, respectively. The degree of mineralization of OTC was 49%, 58%, 55%, 50%, 50% and 68% at control, 10 mM Cl-, SO42-, NO3-, CO32- and HCO3-, respectively. The degree of mineralization of TC was 66%, 76%, 65%, 60%, 74% and 43% at control, 100 mM Cl-, SO42-, NO3-, CO32- and HCO3-, respectively. The degree of mineralization of OTC was 49%, 45%, 48%, 43%, 42% and 63% at control, 100 mM Cl-, SO42-, NO3-, CO32- and HCO3-, respectively. When tetracycline and oxytetracycline mineralization were compared, tetracycline mineralization was higher. Inorganic anions affected the mineralization of tetracycline and oxytetracycline. While inorganic anions (Cl-, SO42-, NO3-, CO32- and HCO3-) did not affect degradation of tetracycline and oxytetracycline up to 100 mM concentration, mineralization was affected in both directions (increasing and decreasing) at different ion concentrations.
Keywords: Fenton process; Degradation; Mineralization; Inorganic anions